Surgical lung biopsy for the diagnosis of interstitial lung disease in England: 1997-2008 - Hutchinson, John P.; McKeever, Tricia M.; Fogarty, Andrew W.; Navaratnam, Vidya; Hubbard, Richard B. (European Respiratory Society, 2016)
Introduction: International guidelines and new targeted therapies for idiopathic pulmonary fibrosis have increased the need for accurate diagnosis of interstitial lung disease, which may lead to more surgical lung biopsies. This study aims to assess the risk of this procedure in patients from the United Kingdom.